Viver sobre dolinas: a realidade dos moradores dos bairros Vazante Sul e Sebastiana Alves II do município de Vazante, Minas Gerais - Santos, Nathália Ohana Ferreira (2020)
In contemporary times there are many risks and dangers that surround people's lives. These sometimes put the subjects in a situation of vulnerability, in addition to permeating the daily life with negative surprises. In the city of Vazante, state of Minas Gerais, Brazil, the risks that have pervaded time, especially in recent decades, are the appearance of dolines. The dolines are abatements that materialize in the landscape without showing significant previous signs. The event is always accompanied by the surprise effect, given that people and the Municipal Administration itself are unable to predict precisely and in advance the location that will be affected. We understand that they are a type of characteristic feature of the Karstic System, which establishes a direct relationship between the underground environment and the superficial features of the Vazante landscape. However, what is worrying in this context is the fact that two neighborhoods, Vazante Sul and Sebastiana Alves II - from the Government Program “Minha casa Minha vida” - have been affected, putting lives in risk. When the residents become affected, because their house or the street has been succumbed to by a dolina, there are several developments that will accompany them. For this reason, we aim, through this research, to understand what it means to live on dolines, a condition that forces residents to be alert at all times. In addition to putting them before a dialectic, where fear and risk acceptance to remain in place is a constant. The fear of losing the house and becoming homeless is a constant, and consequently, causes insecurity distrust to residents in relation to the place they are residing. Many people have fear for the lives of their family, friends or neighbors. On the other side we find persons who are calm confronting this reality that surrounds them, they believe that it is a natural process where little can be done. In this scenario it was necessary to understand what are the conditions for the appearance of dolines in the city soil. That conditions of doline’s appearance added with the reality narrated by the residents give us the allow to achieve the proposed object.